RANCANGAN BUKU SAKU KEANEKARAGAMAN TUMBUHAN SPERMATOPHYTA PADA MATERI PLANTAE KELAS X SMA - Theopani Sihombing; Yuslim Fauziah; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : This study aims to design a Pocket Book Of Plants Spermatophyta in high school biology learning Class X Plantae material as one of the learning resources in the form of pocket books. This research was conducted at the Faculty of teacher training and Education, University of Riau in September-December 2021. The foundation in the stages of designing this pocket book is the curriculum analysis stage and the pocket book design stage. The curriculum analysis phase is carried out by reviewing the 2013 curriculum and analyzing learning materials. Pocket book design phase is done by designing the syllabus and lesson plan first then do the pocket book design, where the pocket book design consists of cover, preface, table of contents, curriculum level, usage guide, Introduction, contents, and bibliography. The type of research used is descriptive qualitative where the method used is the survey method. Based on the analysis of the potential there are as many as 26 species of plants spermatophyta in the Arboretum of Riau University that can be used as a pocket book design on the material plantae in biology learning Class X SMA.Key Words : Pocket Book, Learning Media, Spermatophyta Plants